Method for reducing roughness of gravure silver wire electrode and its application

By coating the fluid of functional material on the surface of the gravure printing silver wire electrode to fill its concave area, the problem of high roughness of the silver wire electrode is solved, and high-performance preparation and mass production of flexible organic solar cells are achieved.

CN114361348BActive Publication Date: 2025-04-18SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011387914.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-12
Filing Date
2020-12-01
Publication Date
2025-04-18
Estimated Expiration
2040-12-01

AI Technical Summary

Technical Problem

The roughness of the gravure printed silver wire electrode is relatively large, which leads to the problem of device leakage or short circuit in the preparation of flexible organic solar cells.

Method used

The surface of the silver wire electrode is coated with a fluid containing a functional material so that the functional material fills the concave area of ​​the surface of the silver wire electrode, thereby reducing its surface roughness.

Benefits of technology

It effectively reduces the surface roughness of the silver wire electrode, makes it suitable for the preparation of flexible organic solar cells, reduces the risk of device leakage or short circuit, and supports large-scale preparation and patterned production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002810282150000071
    Figure BDA0002810282150000071
  • Figure BDA0002810282150000081
    Figure BDA0002810282150000081
  • Figure BDA0002810282150000091
    Figure BDA0002810282150000091
Patent Text Reader

Abstract

The present invention discloses a method for reducing the roughness of a gravure silver wire electrode and its application. The method for reducing the roughness of a gravure silver wire electrode comprises: manufacturing a silver wire electrode by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure; coating a fluid containing a functional material on the surface of the silver wire electrode, and at least allowing the functional material to fill the concave area on the surface of the silver wire electrode, thereby reducing the surface roughness (RMS) of the silver wire electrode to less than 5nm. The present invention can effectively reduce the surface roughness of the gravure printed silver wire electrode, so that the silver wire electrode can be directly patterned and mass-produced by the gravure printing method, and can well meet the requirements for preparing high-performance flexible organic solar cells, which is conducive to the subsequent integration of the entire preparation process of the flexible organic solar cell, and realizes the efficient, high-quality and low-cost production of the flexible organic solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a method for reducing the roughness of a gravure silver wire electrode and an application thereof, for example, an application in preparing a flexible organic solar cell. Background Art

[0002] Flexible organic solar cells are an important direction for the development of solar cells and have great application potential. Flexible transparent electrodes are an important prerequisite for the development of flexible organic solar cells. Traditional ITO materials have fatal defects, such as fragility and difficulty in flexibility. In order to prepare high-performance flexible transparent electrodes, people have studied materials such as graphene, carbon nanotubes, conductive polymers, metal grids, and silver nanowires. Since silver nanowires have the advantages of high conductivity, high transmittance, excellent bending performance, and solution-based roll-to-roll mass production, they have received widespread attention and research, becoming the most popular material for preparing flexible transparent electrodes.

[0003] At present, the silver wire electrodes used to prepare flexible organic solar cells are usually prepared by spin coating. The silver wire electrodes prepared by spin coating cannot be patterned, but need to be etched and patterned before they can be used to prepare organic solar cells. In addition, it is difficult to prepare silver wire electrodes in large areas and in large quantities by spin coating.

[0004] Some researchers have used gravure printing to prepare silver wire electrodes, which has the advantage that they can be pre-patterned and can be prepared in large areas and in large quantities. However, compared with the currently common slot die and spin coating processes, gravure printing uses a "dot-type" design, that is, the silver nanowire ink is first loaded into independent mesh cells and then re-fused on the substrate. The film quality depends on the effect of the re-fusion of these dots, and there is a high probability of periodic unevenness at the scale of 100-200 microns. In addition, the roughness of the silver wire electrode printed by gravure printing is relatively large (essentially a hollow conductive network with a height difference of more than 100nm), so it is not suitable for the preparation of flexible organic solar cells. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for reducing the roughness of a gravure silver wire electrode and its application in preparing a flexible organic solar cell, thereby overcoming the shortcomings of the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] An embodiment of the present invention provides a method for reducing the roughness of a gravure printed silver wire electrode, comprising:

[0008] The silver wire electrode is manufactured by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure;

[0009] A fluid containing a functional material is coated on the surface of the silver wire electrode, and the functional material at least fills the concave area on the surface of the silver wire electrode, thereby reducing the surface roughness of the silver wire electrode.

[0010] Furthermore, the surface roughness (RMS) of the silver wire electrode is reduced to below 5 nm.

[0011] In some embodiments, the method for reducing the roughness of the gravure silver wire electrode specifically includes: coating a fluid containing a functional material on the surface of the silver wire electrode, so that the functional material fills the concave area on the surface of the silver wire electrode and also forms a functional material layer on the surface of the silver wire electrode.

[0012] An embodiment of the present invention further provides a method for preparing a flexible organic solar cell, comprising the steps of respectively preparing a first electrode, an active layer, and a second electrode; wherein the step of preparing any one of the first electrode and the second electrode comprises:

[0013] The silver wire electrode is formed by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure;

[0014] A fluid containing a functional material is coated on the surface of the silver wire electrode, so that the functional material fills the concave area on the surface of the silver wire electrode and forms a functional material layer on the surface of the silver wire electrode.

[0015] In some embodiments, the functional material layer has a flat surface.

[0016] The embodiments of the present invention also provide a flexible organic solar cell prepared by any of the aforementioned methods.

[0017] Compared with the prior art, the beneficial effect of the technical solution provided by the embodiment of the present invention is at least that: the surface roughness of the gravure-printed silver wire electrode can be effectively reduced, so that the silver wire electrode can be directly patterned and mass-produced by the gravure printing method, and can also well meet the requirements for preparing high-performance flexible organic solar cells, which is conducive to the subsequent integration of the entire preparation process of the flexible organic solar cell. For example, the production of the entire flexible organic solar cell can be realized through a set of multi-color overprinting system. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be described in more detail below in conjunction with specific implementations.

[0019] It should be noted that, unless otherwise specifically stated, the use of the terms "include, include, including", "have, has or having" should generally be understood to be open-ended and non-restrictive. Also, it should be understood that the order of the steps or the order in which a particular action is performed is not very important, as long as the teachings of the present invention remain operable. In addition, two or more steps or actions may be performed simultaneously.

[0020] As mentioned above, although some researchers have used gravure printing to make silver wire electrodes based on silver nanowires, it is not suitable for use in flexible organic solar cells. The main reason is that the surface roughness of the silver wire electrodes made by the gravure printing method is too large. When used to make flexible organic solar cells, it is very likely to cause device leakage or short circuit.

[0021] An aspect of an embodiment of the present invention provides a method for reducing the roughness of a gravure printed silver wire electrode, comprising:

[0022] The silver wire electrode is manufactured by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure;

[0023] A fluid containing a functional material is coated on the surface of the silver wire electrode, and the functional material at least fills the concave area on the surface of the silver wire electrode, thereby reducing the surface roughness of the silver wire electrode.

[0024] The silver wire electrode can be considered as a porous network structure formed by interweaving silver nanowires, and the concave areas on the surface of the silver wire electrode include but are not limited to pits caused by uneven fusion of gravure printing dots and holes on the surface of the porous network structure. The presence of these concave areas makes the surface of the silver wire electrode have a large height difference, that is, a large surface roughness. In the embodiment of the present invention, by filling these concave areas with the above-mentioned functional materials, the surface roughness of the silver wire electrode can be effectively reduced, thereby reducing or even eliminating the risk of device leakage or short circuit when the silver wire electrode is used to make a flexible organic solar cell.

[0025] Furthermore, in order to avoid the adverse effects of the aforementioned functional materials on the functions of the silver wire electrodes, the resistivity range of the functional materials is selected to be 10 -3 ~10 6 Ω.m, preferably 10 -1 ~10 4 Ω.m.

[0026] Furthermore, in order to allow the functional material to smoothly enter the concave areas on the surface of the silver wire electrode and fully fill these concave areas, the viscosity of the fluid containing the functional material is selected to be in the range of 2 to 1000 mPa.s, preferably 2 to 300 mPa.s. At the same time, the surface tension of the fluid containing the functional material is selected to be in the range of 20 to 50 mN / m.

[0027] Furthermore, the concentration range of the functional material in the fluid containing the functional material is selected to be 5 to 100 mg / mL, preferably 10 to 50 mg / mL.

[0028] Furthermore, the material of the functional material includes inorganic material, organic material or inorganic-organic composite material. For example, the inorganic material includes ZnO, TiO 2 SnO 2 Any one or more combinations of, and not limited to. For example, the organic material includes a conductive polymer (such as PEDOT:PSS, etc., and not limited to this). For example, the inorganic-organic composite material includes a ZnO:PEI composite material, a ZnO:PVP composite material, a PEI-Zn composite material (Fei Qin et al., Nature Communications, 2020, volume 11, p4508), and is not limited to this.

[0029] Furthermore, the fluid containing the functional material is a dispersion of an inorganic nanomaterial, or the fluid containing the functional material is an inorganic-organic composite material solution, a conductive polymer solution, etc. For example, the inorganic nanomaterial includes but is not limited to ZnO nanoparticles, TiO 2 Nanoparticles, SnO 2 Nanoparticles, etc. For example, the inorganic-organic composite material includes but is not limited to ZnO:PEI solution, ZnO:PVP solution, PEI-Zn solution, etc. For example, the conductive polymer solution can be a PEDOT:PSS solution, etc. (Clevios HIL-E100 conductive polymer of HERAEUS can be selected).

[0030] In particular, the particle size of the functional material is within 150 nm, preferably within 20 nm. Since the fluid containing the functional material is a solution or the functional material contained is nano-scale particles, it can well fill the silver nanowire network and achieve the effect of reducing roughness.

[0031] In some embodiments, the method for reducing the roughness of the gravure silver wire electrode specifically includes: coating a fluid containing a functional material on the surface of the silver wire electrode, so that the functional material fills the concave area on the surface of the silver wire electrode and also forms a functional material layer on the surface of the silver wire electrode.

[0032] Furthermore, the thickness range of the functional material layer is selected to be between 20 and 150 nm, preferably between 40 and 100 nm. And the surface of the functional material layer is flat. By forming the aforementioned thicker functional material layer, not only can the purpose of filling the surface depression of the silver wire electrode to reduce its surface roughness be achieved, but the functional material layer can also form a good energy level match with the upper and lower layers in the device structure such as flexible organic solar cells, and the functional material layer can also improve the wettability of the interface of the thin film and improve the film forming quality of the upper thin film.

[0033] In some embodiments, the method for reducing the roughness of the gravure silver wire electrode specifically includes: coating the fluid containing the functional material on the surface of the silver wire electrode by at least one of spin coating, gravure printing, spray coating, inkjet printing, and screen printing, or a combination of multiple methods.

[0034] In some embodiments, the sheet resistance of the silver wire electrode is 5 to 150 Ω / □.

[0035] Another aspect of an embodiment of the present invention provides a method for preparing a flexible organic solar cell, comprising steps of respectively preparing a first electrode, an active layer, and a second electrode; wherein the step of preparing any one of the first electrode and the second electrode comprises:

[0036] The silver wire electrode is formed by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure;

[0037] A fluid containing a functional material is coated on the surface of the silver wire electrode, so that the functional material fills the concave area on the surface of the silver wire electrode and forms a functional material layer on the surface of the silver wire electrode.

[0038] Furthermore, the resistivity of the functional material is selected to be 10 -3 ~10 6 Ω.m, preferably 10 -1 ~10 4 Ω.m.

[0039] Furthermore, the viscosity of the fluid containing the functional material is selected to be 2 to 1000 mPa.s, preferably 2 to 300 mPa.s.

[0040] Furthermore, the surface tension of the fluid containing the functional material is 20 to 50 mN / m.

[0041] Furthermore, the concentration of the functional material in the fluid containing the functional material is 5 to 100 mg / mL, preferably 10 to 50 mg / mL.

[0042] Furthermore, the material of the functional material includes inorganic material, organic material or inorganic-organic composite material. For example, the inorganic material includes ZnO, TiO 2 SnO 2 Any one or more combinations thereof are included, but are not limited thereto. For example, the organic material includes a conductive polymer (such as PEDOT:PSS, etc., but are not limited thereto). For example, the inorganic-organic composite material includes a ZnO:PEI composite material, a ZnO:PVP composite material, a PEI-Zn composite material, but are not limited thereto.

[0043] Furthermore, the fluid containing the functional material is a dispersion of an inorganic nanomaterial, or the fluid containing the functional material is an inorganic-organic composite material solution, a conductive polymer solution, etc. For example, the inorganic nanomaterial includes but is not limited to ZnO nanoparticles, TiO 2 Nanoparticles, SnO 2 Nanoparticles, etc. For example, the inorganic-organic composite material includes but is not limited to ZnO:PEI solution, ZnO:PVP solution, PEI-Zn solution, etc. For example, the conductive polymer solution can be a PEDOT:PSS solution, etc. (Clevios HIL-E100 conductive polymer from HERAEUS can be used).

[0044] Furthermore, the particle size of the functional material is within 150 nm, preferably within 20 nm.

[0045] Furthermore, the thickness of the functional material layer is between 20 and 150 nm, and preferably between 40 and 100 nm.

[0046] Furthermore, the surface of the functional material layer is flat.

[0047] In some cases, the functional material layer also serves as an electron transport layer or a hole transport layer.

[0048] Furthermore, the silver wire electrode is a flexible transparent electrode formed on a flexible transparent film, and the flexible transparent film includes but is not limited to PET (polyethylene terephthalate), PI (polyimide) or PEN (polyethylene naphthalate) film and the like.

[0049] Furthermore, the square resistance of the silver wire electrode is 5 to 150Ω / □.

[0050] Furthermore, the flexible organic solar cell may also include other known structural layers or components.

[0051] In some embodiments, the preparation method further includes: a step of making an electron transport layer, wherein the electron transport layer is disposed between the first electrode and the active layer.

[0052] In some embodiments, the preparation method further includes: a step of making a hole transport layer, wherein the hole transport layer is disposed between the active layer and the second electrode.

[0053] Furthermore, the electron transport layer, active layer, hole transport layer, etc. can be prepared using corresponding materials known in the art.

[0054] For example, the material of the electron transport layer includes ZnO, TiO 2 SnO 2 , PFN, PFNBr, PDINO, any one or more combinations thereof, and not limited thereto.

[0055] For example, the material of the active layer includes any one or more combinations of PM6, PTB7-Th, PCBM, IT-4F, Y6, and N3, but is not limited thereto.

[0056] For example, the material of the hole transport layer includes any one or more combinations of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly-3,4-ethylenedioxythiophene / polystyrene sulfonate, nickel oxide, copper oxide, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, cuprous thiocyanate, and molybdenum oxide, and is not limited thereto.

[0057] Furthermore, the other of the first electrode and the second electrode includes any one or more combinations of metal electrodes (such as Ag electrodes, Al electrodes, Au electrodes, Cu electrodes, etc.), PH1000 polymer electrodes, and metal oxide electrodes, but is not limited thereto.

[0058] In addition, the electron transport layer, the hole transport layer, the active layer and the other of the first electrode and the second electrode can be prepared by methods known in the art, such as a solution method or an evaporation method.

[0059] Another aspect of the embodiments of the present invention provides a flexible organic solar cell prepared by any of the aforementioned methods.

[0060] Furthermore, the flexible organic solar cell may include a bottom electrode (flexible transparent silver wire electrode), a functional material layer, an electron transport layer, an active layer, a hole transport layer, and a top electrode, which are arranged in sequence from bottom to top. In some cases, the functional material layer also has the function of an electron transport layer, so that the electron transport layer can be omitted. Alternatively, the flexible organic solar cell may also include a bottom electrode (flexible transparent silver wire electrode), a functional material layer, a hole transport layer, an active layer, an electron transport layer, and a top electrode, which are arranged in sequence from bottom to top. In some cases, the functional material layer also has the function of a hole transport layer, so that the hole transport layer can be omitted. The top electrode and the bottom electrode may be named as the first electrode and the second electrode, respectively, or, conversely, the bottom electrode and the top electrode may be named as the first electrode and the second electrode, respectively.

[0061] The technical solution of the present invention will be described in more detail below in conjunction with several embodiments. It should be noted that, unless otherwise specified, the raw materials, chemical reagents and equipment used in the following embodiments can be obtained through market purchase and other channels, and operations such as gravure printing and spin coating can be implemented according to methods known in the art.

[0062] Embodiment 1 A method for preparing a flexible organic solar cell comprises the following steps:

[0063] 1) Using silver nanowire ink, a patterned silver wire electrode was prepared on a PET film by gravure printing. The silver wire electrode had a square resistance of 17.7Ω / □, a transmittance of 97.2%, and a roughness (AFM test area 10×10μm) RMS of about 11nm. The silver wire electrode was cut into a suitable size and attached to the glass with double-sided tape.

[0064] 2) In an air environment, a methanol solution of zinc oxide nanoparticles with a solid content of 5 mg / mL, 10 mg / mL, 15 mg / mL, 50 mg / mL, and 100 mg / mL (the particle size of the zinc oxide nanoparticles is about 5 nm) was spin-coated on the aforementioned silver wire electrode at a spin coating speed of about 900 r / min, and then annealed on a hot plate at 125° C. for 10 min in a nitrogen environment in a glove box to obtain a zinc oxide film.

[0065] 3) Spin-coating a PM6:Y6 active layer solution on the surface of the zinc oxide film, wherein the PM6 content is 7 mg / mL, the Y6 content is 8.4 mg / mL, and the CN:CF volume ratio is 0.5:99.5, and the spin-coating speed is 2000 r / min. Then, annealing is performed on a hot plate at 100° C. for 10 min in a nitrogen environment in a glove box to obtain an active layer film.

[0066] 4) MoO with a thickness of about 10 nm is sequentially deposited on the active layer film. 3Thin film and Al with a thickness of about 100nm, finally a flexible organic solar cell is obtained.

[0067] Comparative Example 1: The method for preparing a flexible organic solar cell provided in this comparative example is basically the same as that in Example 1, except that:

[0068] Step 2) is not included, and in step 3), the PM6:Y6 active layer solution is directly spin-coated on the surface of the silver wire electrode, and then annealing treatment and other operations are performed to form an active layer film.

[0069] The performance of the flexible organic solar cell devices prepared in Example 1 and Comparative Example 1 (defined as devices 1-1, 1-2, 1-3, 1-4, 1-5, and 1', respectively) was tested. The results are shown in Table 1.

[0070] Table 1

[0071]

[0072] It can be seen from Table 1 that when the solid content of zinc oxide is 15 mg / mL, the zinc oxide film prepared by spin coating can cover the silver wire electrode well, the film thickness is appropriate, the device efficiency is the highest, and an efficiency of 15.28% is obtained. When the solid content of zinc oxide is low (5 mg / mL), the film prepared by spin coating is thinner and cannot cover the silver wire electrode well, resulting in low device performance. When the solid content of zinc oxide is high (100 mg / mL), the film prepared by spin coating is thicker, which will affect the performance of the device. The comparative example is not modified with functional materials, the roughness of the silver wire electrode is too high, and the active layer is directly spin-coated, and the device performance is very poor.

[0073] Embodiment 2 A method for preparing a flexible organic solar cell comprises the following steps:

[0074] 1) Using silver nanowire ink, a patterned silver wire electrode was prepared on a PET film by gravure printing. The square resistance of the silver wire electrode was 17.7Ω / □, the corresponding transmittance was 97.2%, and the roughness (AFM test area 10×10μm) RMS was about 11nm. The silver wire electrode was cut into a suitable size and attached to the glass with double-sided tape.

[0075] 2) In an air environment, a zinc oxide nanoparticle methanol solution with a solid content of about 15 mg / mL (the particle size of the zinc oxide nanoparticles is about 5 nm) is spin-coated on the silver wire electrode at a spin-coating speed of 200 r / min, 400 r / min, 800 r / min, 1000 r / min, 2000 r / min, and 4000 r / min, respectively. Then, the solution is annealed at 125° C. on a hot plate in a nitrogen environment in a glove box for 10 min to obtain zinc oxide films with thicknesses of 150 nm, 100 nm, 50 nm, 40 nm, 20 nm, and 10 nm, respectively.

[0076] 3)~4): The operation is the same as steps 3)~4) of Example 1.

[0077] The performance of the flexible organic solar cell devices (named as devices 2-1, 2-2, 2-3, 2-4, 2-5, and 2-6, respectively) prepared in Example 2 was tested. The results are shown in Table 2.

[0078] Table 2

[0079]

[0080] It can be seen from Table 2 that when the thickness of the zinc oxide film is 50nm, the efficiency of the prepared device is the highest at 15.05%. This is because the thickness of the zinc oxide film is appropriate and can cover the silver wire electrode well. When the zinc oxide film is thicker (150nm), the current Jsc of the device is significantly reduced, and the filling FF is also slightly reduced, resulting in low device efficiency. When the zinc oxide film is thinner (10nm), the zinc oxide film cannot cover the silver wire electrode well, resulting in poor performance of the device.

[0081] Embodiment 3: A method for preparing a flexible organic solar cell, comprising the following steps:

[0082] 1) Using silver nanowire ink, a patterned silver wire electrode was prepared on a PET film by gravure printing. The square resistance of the silver wire electrode was 10.8Ω / □, the corresponding transmittance was 95.4%, and the roughness (AFM test area 10×10μm) RMS was 12nm. The silver wire electrode was cut into a suitable size and attached to the glass with double-sided tape.

[0083] 2) In an air environment, ZnO:PVP solutions with viscosities of 2mPa.s, 10mPa.s, 300mPa.s, 1000mPa.s, and 2000mPa.s were gravure printed on the silver wire electrode (the solvent was n-butanol and ethanol in a volume ratio of 1:1, and the surface tension was about 24mN / m). Then, the solution was annealed at 125°C on a hot plate in a nitrogen environment in a glove box for 10 minutes to obtain a conductive polymer film with a thickness of 50nm.

[0084] 3)~4): The operation is the same as steps 3)~4) of Example 1.

[0085] The performance of the flexible organic solar cell devices (named as devices 3-1, 3-2, 2-3, 3-4, and 3-5, respectively) prepared in Example 2 was tested. The results are shown in Table 3.

[0086] Table 3

[0087]

[0088] It can be seen from Table 3 that when the viscosity of the ZnO:PVP solution is maintained at 2-300mPa.s, the performance of the device is relatively good. When the viscosity increases to 1000mPa.s, the filling FF of the device begins to decrease significantly, and the device performance decreases. When the viscosity increases to 2000mPa.s, the device performance decreases significantly, which may be due to the high viscosity of the solution, resulting in obvious defects in the formed ZnO:PVP film.

[0089] Embodiment 4: A method for preparing a flexible organic solar cell comprises the following steps:

[0090] 1) Using silver nanowire ink, a patterned silver wire electrode was prepared on a PET film by spraying. The silver wire electrode had a square resistance of 48.0Ω / □, a transmittance of 98.9%, and a roughness (AFM test area 10×10μm) RMS of about 10nm. The silver wire electrode was cut into a suitable size and attached to the glass with double-sided tape.

[0091] 2) In an air environment, a methanol solution of zinc oxide nanoparticles with a solid content of 15 mg / mL was spin-coated on the aforementioned silver wire electrode, the particle sizes of the zinc oxide nanoparticles in each solution were about 1 nm, 5 nm, 20 nm, and 150 nm, respectively, and the spin coating speed was about 800 r / min. Then, the solution was annealed on a hot plate at 125° C. for 10 min in a nitrogen environment in a glove box to obtain a zinc oxide film with a thickness of about 50 nm.

[0092] 3)~4): The operation is the same as steps 3)~4) of Example 1.

[0093] The performance of the flexible organic solar cell devices (named as devices 4-1, 4-2, 4-3, and 4-4, respectively) prepared in Example 2 was tested. The results are shown in Table 4.

[0094] Table 4

[0095]

[0096] It can be seen from Table 4 that when the zinc oxide particle size is within 20nm, the device performance is relatively good. When the zinc oxide particle size is larger (150nm), the device performance is significantly reduced, which may be due to the presence of some voids in the film formed when the zinc oxide particles are too large.

[0097] Comparative Example 2: A method for preparing a flexible organic solar cell is substantially the same as that of Example 1, except that:

[0098] In step (2), the methanol solution of zinc oxide nanoparticles was replaced by a PDMS solution having a concentration of 10 mg / mL.

[0099] The performance of the flexible organic solar cell device prepared in Comparative Example 2 was tested, and the results showed that the device was not conducting, which may be due to the high resistivity and poor conductivity of the PDMS film.

[0100] Comparative Example 3: A method for preparing a flexible organic solar cell is substantially the same as that of Example 1, except that:

[0101] In step (2), the methanol solution of zinc oxide nanoparticles was replaced by a Clevios PH1000 polymer solution with a concentration of 10 mg / mL.

[0102] The performance of the flexible organic solar cell device prepared in Comparative Example 3 was tested, and the results showed that the effective area of ​​the device was significantly increased, which may be due to the excellent conductivity of the PH1000 polymer.

[0103] Embodiment 5: A method for preparing a flexible organic solar cell comprises the following steps:

[0104] 1) Using silver nanowire ink, a patterned silver wire electrode was prepared on a PET film by gravure printing. The square resistance of the silver wire electrode was 17.7Ω / □, the corresponding transmittance was 97.2%, and the roughness (AFM test area 10×10μm) RMS was about 11nm. The silver wire electrode was cut into a suitable size and attached to the glass with double-sided tape.

[0105] 2) In air environment, spin-coat poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS, 4083) on the silver wire electrode at a spin-coating speed of 500r / min, 1000r / min, and 3000r / min, respectively. Then anneal on a hot plate at 130°C for 10min in air environment to obtain PEDOT:PSS films with thicknesses of 150nm, 80nm, and 40nm, respectively.

[0106] 3) Spin-coat the surface of the PEDOT:PSS film with a PM6:Y6 active layer solution, wherein the PM6 content is 7 mg / mL, the Y6 content is 8.4 mg / mL, and the CN:CF volume ratio is 0.5:99.5, at a spin-coating speed of 2000 r / min, and then anneal on a hot plate at 100°C for 10 min in a nitrogen environment in a glove box to obtain an active layer film.

[0107] 4) A PDINO film with a thickness of about 15 nm and an Al film with a thickness of about 100 nm are sequentially spin-coated on the active layer film to finally obtain a flexible organic solar cell.

[0108] The performance of multiple flexible organic solar cell device samples (named as device 5-1, 5-2, and 5-3, respectively) prepared in Example 5 was tested. The results are shown in Table 5.

[0109] Table 5

[0110]

[0111] It can be seen from Table 5 that when the thickness of the PEDOT film is 80nm, the efficiency of the prepared device is the highest at 15.26%. This is because the thickness of the PEDOT film is appropriate at this time, which can well cover the silver wire electrode and reduce its surface roughness. When the zinc oxide film is thicker (150nm), the current Jsc of the device is significantly reduced, and the filling FF is also slightly reduced, resulting in low device efficiency. When the zinc oxide film is thinner (40nm), the zinc oxide film cannot well cover the silver wire electrode and reduce its surface roughness, resulting in poor performance of the device.

[0112] Embodiment 6: A method for preparing a flexible organic solar cell comprises the following steps:

[0113] 1) Using silver nanowire ink, a patterned silver wire electrode was prepared on a PET film by gravure printing. The square resistance of the silver wire electrode was 17.7Ω / □, the corresponding transmittance was 97.2%, and the roughness (AFM test area 10×10μm) RMS was about 11nm. The silver wire electrode was cut into a suitable size and attached to the glass with double-sided tape.

[0114] 2) In air environment, spin-coat poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS, 4083) on the silver wire electrode at a spin-coating speed of 500r / min, 1000r / min, and 3000r / min, respectively. Then anneal on a hot plate at 130°C for 10min in air environment to obtain PEDOT:PSS films with thicknesses of 150nm, 80nm, and 40nm, respectively.

[0115] 3) Spin-coat a zinc oxide nanoparticle methanol solution with a solid content of about 15 mg / mL (the particle size of the zinc oxide nanoparticles is about 5 nm) on the surface of the PEDOT:PSS film at a spin-coating speed of 2000 r / min. Then anneal at 125°C for 10 min on a hot plate in a nitrogen environment in a glove box to obtain a zinc oxide film with a thickness of about 20 nm.

[0116] 4) Spin-coating a PM6:Y6 active layer solution on the surface of the zinc oxide film, wherein the PM6 content is 7 mg / mL, the Y6 content is 8.4 mg / mL, and the CN:CF volume ratio is 0.5:99.5, and the spin-coating speed is 2000 r / min. Then, annealing is performed on a hot plate at 100° C. for 10 min in a nitrogen environment in a glove box to obtain an active layer film.

[0117] 5) MoO with a thickness of about 10 nm is sequentially deposited on the active layer film. 3Thin film and Al with a thickness of about 100nm, finally a flexible organic solar cell is obtained.

[0118] The performance of the flexible organic solar cell devices (named as devices 6-1, 6-2, and 6-3, respectively) prepared in Example 6 was tested. The results are shown in Table 6.

[0119] Table 6

[0120]

[0121] It can be seen from Table 6 that when the thickness of the PEDOT film is 80nm, the efficiency of the prepared device is the highest at 15.26%. This is because the thickness of the PEDOT film is appropriate at this time and can fill the silver wire electrode well. When the zinc oxide film is thicker (150nm), the current Jsc of the device is significantly reduced, and the filling FF is also slightly reduced, resulting in low device efficiency. When the zinc oxide film is thinner (40nm), the zinc oxide film cannot fill the silver wire electrode well, and the roughness of the silver wire electrode is still relatively large, resulting in the zinc oxide film not being able to cover the silver wire electrode well, resulting in poor performance of the device.

[0122] The ZnO nanoparticles in the above embodiments of the present invention can also be replaced by TiO 2 Nanoparticles, SnO 2 Nanoparticles, etc. ZnO:PVP solution can also be replaced by ZnO:PEI solution, PEI-Zn solution, etc. or PEDOT:PSS solution, etc.

[0123] In the above embodiments of the present invention, the active layer, the hole transport layer, etc. can also be made of other materials known in the art. The active layer can also be formed by PM6, PTB7-Th, PCBM, IT-4F, Y6, N3, etc., and the hole transport layer can also be formed by self-poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine], poly 3,4-ethylenedioxythiophene / polystyrene sulfonate, nickel oxide, copper oxide, 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene, cuprous thiocyanate, molybdenum oxide, etc. The remaining electrodes except the silver wire electrode can also be Ag electrodes, Al electrodes, Au electrodes, Cu electrodes, PH1000 polymer electrodes, metal oxide electrodes, etc.

[0124] The technical solutions provided in the above embodiments of the present invention can effectively reduce the surface roughness of the gravure-printed silver wire electrodes, so that the silver wire electrodes can be directly patterned and mass-produced by the gravure printing method, and can well meet the requirements for preparing high-performance flexible organic solar cells, which is conducive to the subsequent integration of the entire preparation process of flexible organic solar cells, and realizes efficient, high-quality and low-cost production of flexible organic solar cells.

[0125] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0126] The use of headings and sections in this invention is not meant to limit the invention; each section may apply to any aspect, embodiment or feature of the invention. Although the invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the invention.

[0127] In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention. Therefore, it is not intended herein to limit the present invention to the specific disclosed embodiments for carrying out the present invention, but it is intended that the present invention will include all embodiments falling within the scope of the appended claims. Furthermore, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather the terms first, second, etc. are used to distinguish one element from another.

Claims

1. A method for reducing the roughness of a gravure silver wire electrode, characterized in that: include: The silver wire electrode is manufactured by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure; Applying a fluid containing a functional material on the surface of the silver wire electrode, so that the functional material fills the concave area on the surface of the silver wire electrode and forms a functional material layer with a smooth surface on the surface of the silver wire electrode, thereby reducing the surface roughness of the silver wire electrode to less than 5 nm; The viscosity of the fluid containing the functional material is 2-1000 mPa.s, the surface tension is 20-50 mN / m, the concentration of the functional material is 5-100 mg / mL, and the resistivity of the functional material is 10 -3 ~10 6 Ω.m, the functional material comprises an inorganic-organic composite material, and the inorganic-organic composite material comprises a ZnO:PEI composite material, a ZnO:PVP composite material or a PEI-Zn composite material.

2. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The resistivity of the functional material is 10 -1 ~10 4 Ω.m.

3. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The viscosity of the fluid containing the functional material is 2-300 mPa.s.

4. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The concentration of the functional material in the fluid containing the functional material is 10-50 mg / mL.

5. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The fluid containing the functional material is an inorganic-organic composite material solution.

6. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The particle size of the functional material is within 150 nm.

7. The method for reducing the roughness of a gravure silver wire electrode according to claim 6, characterized in that: The particle size of the functional material is within 20 nm.

8. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The thickness of the functional material layer is 20-150 nm.

9. The method for reducing the roughness of a gravure silver wire electrode according to claim 8, characterized in that: The thickness of the functional material layer is 40-100 nm.

10. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: Specifically include: The fluid containing the functional material is coated on the surface of the silver wire electrode by at least one of spin coating, gravure printing, spray coating, inkjet printing, and screen printing, or a combination of multiple methods.

11. The method for reducing the roughness of a gravure silver wire electrode according to claim 1, characterized in that: The square resistance of the silver wire electrode is 5-150 Ω / □.

12. A method for preparing a flexible organic solar cell, comprising the steps of separately preparing a first electrode, an active layer and a second electrode; characterized in that: The step of manufacturing any one of the first electrode and the second electrode comprises: The silver wire electrode is formed by gravure printing, wherein the silver wire electrode comprises a silver nanowire network structure; Applying a fluid containing a functional material on the surface of the silver wire electrode, so that the functional material fills the concave area on the surface of the silver wire electrode and forms a functional material layer with a smooth surface on the surface of the silver wire electrode; The viscosity of the fluid containing the functional material is 2-1000 mPa.s, the surface tension is 20-50 mN / m, the concentration of the functional material is 5-100 mg / mL, and the resistivity of the functional material is 10 -3 ~10 6 Ω.m, the functional material comprises an inorganic-organic composite material, and the inorganic-organic composite material comprises a ZnO:PEI composite material, a ZnO:PVP composite material or a PEI-Zn composite material.

13. The preparation method according to claim 12, characterized in that: The resistivity of the functional material is 10 -1 ~10 4 Ω.m.

14. The preparation method according to claim 12, characterized in that: The viscosity of the fluid containing the functional material is 2-300 mPa.s.

15. The preparation method according to claim 12, characterized in that: The concentration of the functional material in the fluid containing the functional material is 10-50 mg / mL.

16. The preparation method according to claim 12, characterized in that: The fluid containing the functional material is an inorganic-organic composite material solution.

17. The preparation method according to claim 12, characterized in that: The particle size of the functional material is within 150 nm.

18. The preparation method according to claim 17, characterized in that: The particle size of the functional material is within 20 nm.

19. The preparation method according to claim 12, characterized in that: The thickness of the functional material layer is 20-150 nm.

20. The preparation method according to claim 19, characterized in that: The thickness of the functional material layer is 40-100 nm.

21. The preparation method according to claim 12, characterized in that: The silver wire electrode is a flexible transparent electrode formed on a flexible transparent film, and the flexible transparent film includes a PET, PI or PEN film.

22. The preparation method according to claim 12, characterized in that: The square resistance of the silver wire electrode is 5-150 Ω / □.

23. The preparation method according to claim 12, characterized in that: The material of the active layer includes any one or more combinations of PM6, PTB7-Th, PCBM, IT-4F, Y6, and N3.

24. The preparation method according to claim 12, characterized in that: The other of the first electrode and the second electrode comprises any one or more combinations of a metal electrode, a conductive polymer electrode, and a metal oxide electrode.

25. The preparation method according to claim 12, characterized in that: Also includes: The step of making an electron transport layer, and / or the step of making a hole transport layer; the electron transport layer is arranged between the first electrode and the active layer, and the hole transport layer is arranged between the active layer and the second electrode.

26. The preparation method according to claim 25, characterized in that: The material of the electron transport layer includes any one or more combinations of ZnO, TiO2, SnO2, PFN, PFNBr, and PDINO.

27. The preparation method according to claim 25, characterized in that: The material of the hole transport layer includes any one or more combinations of self-poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly-3,4-ethylenedioxythiophene / polystyrene sulfonate, nickel oxide, copper oxide, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, cuprous thiocyanate, and molybdenum oxide.

Citation Information

Patent Citations

  • Flexible transparent electrode, preparation method thereof and flexible solar cell prepared from flexible transparent electrode

    CN111192965A

  • Transparent pattern electrode, method of manufacturing the electrode, and organic electronic device using the electrode and its manufacturing method

    JP2011154940A